De Te Fabula Narratur: Marx and Systemism - Guilherme Nunes Pires (Œconomia)
This article argues that the underlying ontological propositions in Marx’s thought is compatible with the main elements of contemporary systemism. Systemism is the ontological conception that affirms that reality is formed by systems of systems. That is, natural or social reality is formed by systems made up of subsystems and each of them has relative autonomy of development and its own dynamics, although interrelated. In this sense, any society is a system with economic, political, and cultural subsystems with relative autonomy of development. No subsystem can completely determine the trajectory of the development of the system as a whole. We argue that Marx’s ontological elements can be interpreted as a form of systemism, contenting the main elements of this contemporary view of social reality. The ontological categories of totality and uneven development are key to understanding Marx’s conception of social reality as a system of systems and steer his thought away from any holist and deterministic interpretation.